The price of the Bermudan option: A simple, explicit formula. Issue 9 (3rd May 2023) - Alghalith, Moawia
Abstract: We introduce a simple, explicit formula for pricing the Bermudan options. Furthermore, the formula does not require any additional parameter (relative to the European option formula). Moreover, we provide an upper bound for the price.